Biomechanical and functional analysis of the shoulder complex and thoracic spine in patients with subacromial impingement syndrome: A case control study. Issue 4 (27th January 2023) - Choi, Moonyoung; Chung, Jinwook
Abstract : The motions of the shoulder are mainly carried out through the glenohumeral joint, but are also assisted by the scapulothoracic joint. Therefore, changes in the biomechanics of the thoracic spine and scapula affect the function of the shoulder. However, there is limited information on the biomechanical and functional characteristics of the shoulder complex and thoracic spine in patients with subacromial impingement syndrome (SIS). In this study, the biomechanical and functional characteristics of the shoulder complex and thoracic spine were analyzed in patients with SIS compared to healthy individuals. A total of 108 participants were included in this study. Participants were classified into 2 groups, the SIS (n = 55) and healthy (n = 53) groups. The shoulder and thoracic range of motion (ROM), scapular position, and isokinetic shoulder strength were measured in all participants. The shoulder ROM was significantly decreased in the SIS group compared to the healthy group ( P < .001). The thoracic spine ROM showed significantly limited extension in the SIS group ( P < .001). The scapular position showed significantly increased anterior tilting ( P = .005), internal rotation ( P = .032), protraction ( P < .001), and decreased upward rotation ( P = .002) in the SIS group. The isokinetic shoulder external rotation ( P < .001) and abduction ( P < .001) strength were significantly lower in the SIS group. Patients with SIS showed reduced shoulder ROM and end-range extension of the thoracic spine compared to healthy individuals, and the scapula was in a more anterior-tilted, protracted, and downward rotated position. In addition, it showed lower external rotation and abduction strength. These results suggest the need for interventions to improve the limited thoracic extension and altered scapular position, which may affect shoulder ROM and muscle strength in the rehabilitation of patients with SIS.